2013
DOI: 10.1111/jep.12075
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics associated with the occurrence of adverse events: a retrospective medical record review using the Global Trigger Tool in a fully digitalized tertiary teaching hospital in Korea

Abstract: The Global Trigger Tool was useful for the detection of adverse events in a Korean hospital setting. Triggers with high positive predictive values should have priority for incorporation into routine screening systems. Furthermore, patients who stay longer in the hospital need to be closely monitored using triggers to improve patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(98 citation statements)
references
References 23 publications
4
89
3
2
Order By: Relevance
“…Concerning the rate of AEs, the results found in our study are higher than those found in other studies: Landrigan et al (2010), Rutberg et al (2014), Rozenfeld, Giordani, and Coelho (2013) Classen et al (2011), the rate of 25.1 AEs per 100 admissions found by Landrigan et al (2010), and the rate of 14.5 AEs per 100 admissions found by Hwang et al (2014). Although the rate of AEs found in this study (31.1%) is slightly lower than that found by Classen et al (2011), 33.3%, it is higher than the rates reported by Landrigan et al (2010), 18.1%, Hwang et al (2014), 7%, and Rutberg et al (2014), 20.5%.…”
Section: Resultscontrasting
confidence: 57%
See 2 more Smart Citations
“…Concerning the rate of AEs, the results found in our study are higher than those found in other studies: Landrigan et al (2010), Rutberg et al (2014), Rozenfeld, Giordani, and Coelho (2013) Classen et al (2011), the rate of 25.1 AEs per 100 admissions found by Landrigan et al (2010), and the rate of 14.5 AEs per 100 admissions found by Hwang et al (2014). Although the rate of AEs found in this study (31.1%) is slightly lower than that found by Classen et al (2011), 33.3%, it is higher than the rates reported by Landrigan et al (2010), 18.1%, Hwang et al (2014), 7%, and Rutberg et al (2014), 20.5%.…”
Section: Resultscontrasting
confidence: 57%
“…Although the rate of AEs found in this study (31.1%) is slightly lower than that found by Classen et al (2011), 33.3%, it is higher than the rates reported by Landrigan et al (2010), 18.1%, Hwang et al (2014), 7%, and Rutberg et al (2014), 20.5%. The significant differences found between the results from the various studies could have been influenced by several factors, such as the organizational structure, the hospital's safety culture, the type of inpatients, the context where the study was carried out, the review process, and the reviewers' training.…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…However, higher ADE rates are generally encountered in the following circumstances: lengthy hospital stay (>7 days) [40], impaired kidney function [41], elderly patients (>65 years) and multiple drug use (>8drugs on day 1) [42]. These factors would need confirmation in further researches.…”
Section: Limitationsmentioning
confidence: 97%
“…Hwang et al [21] identificaram os EA através da GTT e encontraram diferenças estatisticamente significativas entre a identificação dos triggers e a ocorrência dos EA. Dos 13,3% triggers identificados, 10% foram considerados EA.…”
Section: Resultsunclassified